Can the State Listen? Reading Spivak in Indonesia’s Dark Protest 2025 - Setiawan, Rudi (Jurnal Ilmu Kepolisian, 2025)
Gayatri Chakravorty Spivak's classic question, "Can the subaltern speak?" challenges not only the silence produced by colonialism and patriarchy, but also the way modern academic discourse establishes representations of "the other" as a technique of knowledge governance. This article revisits Spivak's argument and the subsequent reflections compiled by Rosalind C. Morris, then integrates them with the contemporary Indonesian context, particularly in the "Indonesia Gelap 2025" demonstration. Using a Cultural Studies approach and a hermeneutic-deconstructive framework, this paper examines how subaltern voices, which often appear as traces, cracks, or performances, attempt to negotiate audibility amid established representational apparatus. The main arguments of this article are: (1) subalternity is not an essential category, but rather a position in power relations that closes access to audibility; (2) "speaking" is not merely a vocal action, but rather an event of recognition in a discursive field that is often curated by the dominant party; (3) in the context of "Indonesia Gelap 2025," various symbolic, performative, and curatorial strategies (ranging from slogans, mass choreography, to happening art) reveal the politics of hearing: who has the right to hear, interpret, and decide. In turn, this article proposes an ethics of listening that transforms the scheme of "giving voice" into a practice of reading-listening that is sensitive to the unspeakable, thus opening up the possibility for subaltern agents to "speak back" without being immediately co-opted by the dominant voice.